DNA repair is limiting for haematopoietic stem cells during ageing. - Nijnik, A; Woodbine, L; Marchetti, C; Dawson, S; Lambe, T; Liu, C; Rodrigues, N; Crockford, T; Cabuy, E; Vindigni, A; Enver, T; Bell, J; et al. (2007)
Accumulation of DNA damage leading to adult stem cell exhaustion has been proposed to be a principal mechanism of ageing. Here we address this question by taking advantage of the highly specific role of DNA ligase IV in the repair of DNA double-strand breaks by non-homologous end-joining, and by the discovery of a unique mouse strain with a hypomorphic Lig4(Y288C) mutation. The Lig4(Y288C) mouse, identified by means of a mutagenesis screening programme, is a mouse model for human LIG4 syndrome, showing immunodeficiency and growth retardation. Diminished DNA double-strand break repair in the Lig4(Y288C) strain causes a progressive loss of haematopoietic stem cells and bone marrow cellularity during ageing, and severely impairs stem cell function in tissue culture and transplantation. The sensitivity of haematopoietic stem cells to non-homologous end-joining deficiency is therefore a key determinant of their ability to maintain themselves against physiological stress over time and to withstand culture and transplantation.